Protocol for 3D photogrammetry and morphological digitization of complex skulls - Naomi De Leo; Claudio Chimenti; Luigi Maiorano; Davide Tamagnini (STAR Protocols)
Summary: Here, we present a protocol for 3D photogrammetry and morphological digitization of skulls, including complex ones with tusks, antlers, and horns, which are challenging to reconstruct digitally. We describe steps for setting up specimens for image acquisition, including camera and lighting configurations, and the subsequent image processing to generate high-quality 3D models. We also outline the extraction of morphological data for accurate geometric morphometric analyses. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.